Comparison of interleukins IL-1β and IL-6 levels, bone mineral density (BMD) and bone metabolism (IBM) in menopausal women - Raciborska, Iwona; Sobczuk, Anna; Tryniszewski, Wiesław; Kozłowska, Magdalena; Górska-Chrząstek, Magdalena; Gadzicki, Mariusz; Maziarz, Zbigniew (Menopause Review/Przegląd Menopauzalny, 2012)
Introduction : Bone metabolism in women is affected among others by estrogens and interleukins. In the menopausal period, the protective effect of estrogens is lowered and production of interleukins IL-1β and IL-6 is significantly increased. Aim : To assess the relation between levels of interleukins IL-1β and IL-6, estradiol and bone mineral density (BMD) and bone metabolism (IBM) in menopausal women. Material and methods : 48 menopausal women, aged 49-61, non-menstruating, without any previous endocrine treatment. Group I comprised 19 women with normal BMD, while group II – 29 women with osteoporosis. Bone densitometry (BMD and bone density T-score). Radioisotope dynamic and static bone scintigraphy and assessment of bone metabolism index (IBM). Serum: interleukins IL-1β and IL-6, Ca+, ALP, P, E2 and TSH. Results : Group I – normal IBM values: 86.2 < IBM < 98.9. Group II – in 40% of subjects, IBM values below normal: 75.1 < IBM < 90.3. Group I – strong positive correlation between BMD and IBM. Group II – moderate positive correlation between BMD and IBM. Group I – normal values of biochemical and hormonal measurements. Group II – insubstantial increase of phosphatase and phosphates concentrations. Interleukin IL-1β and IL-6 levels in group II were significantly higher than in group I (p < 0.0001). Group I – no relation between BMD and interleukin concentrations . Group II – relation between BMD and interleukin concentrations was inversely proportional. Conclusions : In the menopausal period, a reduction of estradiol concentration is accompanied by an increase of bone-resorbing interleukins IL-1β and IL-6, which leads to reduction of body mass and decelerates bone metabolism.